2019
DOI: 10.3329/jbcps.v37i4.43343
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis Adequacy - a Difficult Challenge

Abstract: not available J Bangladesh Coll Phys Surg 2019; 37(4): 165-166

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Dialysis adequacy is important in reducing complications for patients and is influenced by various factors including co-morbidities of patients, economy, distance to DF, supervision of nephrologists. A study in Dhaka, Bangladesh found that patients receiving 12 hours per week of hemodialysis had better adequacy (43%) compared to those receiving only 8 hours (21%) [ 31 ]. According to the KDOQI Guidelines of 2006, incremental HD is suggested to maintain residual renal function at estimated glomerular filtration rate (eGFR) less or equal 15 ml/min/1.73m 2 [ 32 ], while in Bangladesh, most HD patients starts at eGFR of 6–7 ml/min/1.73m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Dialysis adequacy is important in reducing complications for patients and is influenced by various factors including co-morbidities of patients, economy, distance to DF, supervision of nephrologists. A study in Dhaka, Bangladesh found that patients receiving 12 hours per week of hemodialysis had better adequacy (43%) compared to those receiving only 8 hours (21%) [ 31 ]. According to the KDOQI Guidelines of 2006, incremental HD is suggested to maintain residual renal function at estimated glomerular filtration rate (eGFR) less or equal 15 ml/min/1.73m 2 [ 32 ], while in Bangladesh, most HD patients starts at eGFR of 6–7 ml/min/1.73m 2 .…”
Section: Discussionmentioning
confidence: 99%